Gillis Claeissens (1536/37–1605), the Unknown Master from Bruges: Difficulties with the Attribution of Northern Renaissance Portraits - Zvereva, Alexandra A. (Actual Problems of Theory and History of Art, 2016)
The Claeissens family of painters in Bruges has been apparently well known and studied, thanks mainly to a few extant paintings signed by Pieter Claeissens the Elder (1499/1500–1576) and his younger sons Antoon (1541/1542–1613) and Pieter the Younger (c. 1542–1623). Despite the fact that the name of the eldest son Gillis recurs fairly frequently, and his career, seemingly, was more successful than those of his brothers, the absence of any paintings signed by him has considerably complicated the attributions. In 2009, Brecht Dewilde found and published a commission, written in 1576 by Claeis van de Kerchove to Gillis Claeissens, for an epitaph triptych, of which the two side panels are conserved in the Budapest Museum under the name of Pieter Claeissens the Elder. Based on these panels, even while noting the similarity in style between Gillis and his brothers, Dewilde attributed a few more paintings to Gillis which until then had been considered to belong to the other two. Not until the appearance on the Paris art market of a Portrait of an Unknown Gentleman from the 16th Century German School was it possible to discover the full extent of Gillis’ talent and stylistic originality as a portraitist.The study of this painting perfectly illustrates both the necessity of leaving the narrow framework of pure stylistic analysis and the difficulties with the attribution of Northern Renaissance portraits. An art historian should set aside neither the model’s identity, nor the dating of a costume, nor the analysis of the materials such as undercoating and pictorial layers. No matter how meager this information may sometimes seem, these are the elements which make it easier to attribute Renaissance portraits with  certainty, to reconstitute the corpus of each portraitist’s studio, and to reveal later replicas and fakes.
Keywords: Renaissance portrait; Renaissance Bruges; attribution of paintings; Norhtern Renaissance; Flemish painting; Claeissens; state portrait; Gillis Claeissens; Van Brackele